2014
DOI: 10.21608/jalexu.2014.160558
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Some Conventional Insecticides Against Culex Pipiens L. Mosquito Larvae from Different Districts in Egypt

Abstract: The susceptibility of Culex pipiens larvae to some insecticides commonly used in mosquito control programs ]cypermethrin (Sparkill ® ), deltamethrin (Embrator ® ), temephos (Temepest ® ) and spinosad (Tracer ® )[ was investigated, also variations in esterases and glutathione S-transferases (GST) activities among three field populations (Abou homoss, Nadi El Said, Montaza) were measured and compared with a laboratory susceptible strain (S). The highest level of resistance against the tested insecticides was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…pipiens larvae, collected from an agricultural area (Kerdasa, Giza), showed a high level of resistance, although spinosad was very effective against lab strain larvae. These observations agree with those of Moselhy et al (2015), who revealed that the Giza field strain exhibited high RR (11.231 folds) against spinosad at 48 h. This might be due to the intensive application of insecticides in this area, which leads to the development of resistance (Zahran, 2014). Therefore, gemini surfactants may offer feasible alternatives to both plant products and traditional synthetic insecticides.…”
Section: Discussionsupporting
confidence: 91%
“…pipiens larvae, collected from an agricultural area (Kerdasa, Giza), showed a high level of resistance, although spinosad was very effective against lab strain larvae. These observations agree with those of Moselhy et al (2015), who revealed that the Giza field strain exhibited high RR (11.231 folds) against spinosad at 48 h. This might be due to the intensive application of insecticides in this area, which leads to the development of resistance (Zahran, 2014). Therefore, gemini surfactants may offer feasible alternatives to both plant products and traditional synthetic insecticides.…”
Section: Discussionsupporting
confidence: 91%